Dysnatremia and 6-Month Functional Outcomes in Critically Ill Patients With Aneurysmal Subarachnoid Hemorrhage: A Prospective Cohort Study. (8th June 2021) - Cohen, Jeremy; Delaney, Anthony; Anstey, James; Anstey, Matthew; Barge, Deborah; Bellomo, Rinaldo; Bhardwa, Vishnu; Brinkerhoff, Gail; Board, Jasmin; Campain, Anna; Cooper, D. James; Di Tanna, Gian Luca; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To investigate the association between plasma sodium concentrations and 6-month neurologic outcome in critically ill patients with aneurysmal subarachnoid hemorrhage. DESIGN: Prospective cohort study. SETTING: Eleven ICUs in Australia and New Zealand. PARTICIPANTS: Three-hundred fifty-six aneurysmal subarachnoid hemorrhage patients admitted to ICU between March 2016 and June 2018. The exposure variable was daily measured plasma sodium. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Six-month neurologic outcome as measured by the modified Rankin Scale. A poor outcome was defined as a modified Rankin Scale greater than or equal to 4. The mean age was 57 years (± 12.6 yr), 68% were female, and 32% ( n = 113) had a poor outcome. In multivariable analysis, including age, illness severity, and process of care measures as covariates, higher mean sodium concentrations (odds ratio, 1.17; 95% CI, 1.05–1.29), and greater overall variability—as measured by the sd (odds ratio, 1.53; 95% CI, 1.17–1.99)—were associated with a greater likelihood of a poor outcome. Multivariable generalized additive modeling demonstrated, specifically, that a high initial sodium concentration, followed by a gradual decline from day 3 onwards, was also associated with a poor outcome. Finally, greater variability in sodium concentrations was associated with a longer ICU and hospital length of stay: mean ICU length of stay ratio (1.13; 95% CI, 1.07–1.20) and mean hospital length of stay ratio (1.08; 95% CI, 1.01–1.15). CONCLUSIONS: In critically ill aneurysmal subarachnoid hemorrhage patients, higher mean sodium concentrations and greater variability were associated with worse neurologic outcomes at 6 months, despite adjustment for known confounders. Interventional studies would be required to demonstrate a causal relationship.